Adsorptive study of copper (cu2+) in aqueous samples using effervescence amino-zeolite - Jamjoum, Hayfa Alajilani; Kamaruzaman, Sazlinda; Yusof, Nor Azah (Vasile Goldis Western University of Arad, 2021)
Heavy metals, the non-degradable elements of the earth's crust, have many adverse effects on the human body. Their presence in the water environment poses serious health risks to other living organisms as well. Industrial wastewater also contains large amounts of copper ions, which migrate through soil and aquatic streams into the atmosphere and ultimately accumulate along the food chain, causing human beings to face health risks. Excessive human intake of copper ions contributes to severe mucosal irritation and corrosion, hepatic and renal damage, widespread capillary damage, severe gastrointestinal irritation, central nervous system irritation, and potential liver and kidney necrotic changes. Therefore, Cu2+ions are considered for removal. Several products have been used to control sorption contaminants, including granulated activated carbon, EFF-APTES-zeolite, montmorillonite, peat, and compost. The main objective of the current study was to synthesize and characterize EFF-APTES-zeolite using different techniques. The removal of Cu2+ ions was investigated using synthetic solutions at different ion concentrations, contact time, EFF-APTES-zeolite dosage, temperature, and sample pH. The findings of the current study have shown that EFFAPTES-zeolite has been successfully synthesized and characterized by FT-IR, FESEM and BET methods. The results of the current study also showed that the optimal dose for Cu2+ removal was 20 mg with 99.21%, while the optimum concentration was 100 ppm with 99.20%. Similarly, the pH of 4 is the optimum value for EFF-APTES zeolite to extract 99.99% of Cu2+ metal ions from aqueous water. In the meantime, the contact time of 15 min was the optimum period for the successful removal of Cu2+ from aqueous samples. Lastly, 30℃ was noted to be the best temperature for EFF APTES-zeolite to efficiently remove Cu2+ ions (99.69%) from aqueous water. The adsorption kinetics analysis demonstrated a pseudo-first-order and pseudo-second order adsorption model for Cu2+ ions using EFF-APTES-zeolite. This suggests that the adsorption can be regulated by chemical adsorption. Both the Langmuir and Freundlich ii models match the balance data well, suggesting the presence of a monolayer adsorption with a high adsorption potential for Cu2+ at different concentrations.